2000
DOI: 10.1207/s15327752jpa7503_08
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Dependency and Personality Pathology: Variations in Rorschach Oral Dependency Scores Across Axis II Diagnoses

Abstract: Although several investigations have examined the relationship of Rorschach Oral Dependency (ROD; Masling, Rabie, & Blondheim, 1967) scores to Axis I diagnosis, there has been very little research assessing variations in ROD scores across Axis II personality disorders (PDs). In this study, ROD scores were compared in 5 PD groups (borderline PD inpatients, borderline PD outpatients, avoidant-dependent PD outpatients, narcissistic PD outpatients, and antisocial PD outpatients), and 2 non-PD comparison groups (ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Although a number of clinicians and clinical researchers have delineated links between dependency strivings, fears of abandonment, and borderline pathology (e.g., Gunderson, 2007; Lieb et al, 2004), Bornstein, Becker-Matero, Winarick, and Reichman’s (2010) review of the literature on the relationship between performance-based measures of dependency and borderline pathology found that high levels of implicit dependency needs are typically present in BPD-diagnosed inpatients, but not in BPD-diagnosed outpatients. These contrasting patterns may suggest that BP-related dynamics differ somewhat in high- and lower-functioning patients with underlying borderline pathology (see also Bornstein et al, 2000, for evidence bearing on this issue). Alternatively, the experience of hospitalization may exacerbate dependency-related needs and fears in BPD patients, leading to increases in dependent imagery, and increases in ROD scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of clinicians and clinical researchers have delineated links between dependency strivings, fears of abandonment, and borderline pathology (e.g., Gunderson, 2007; Lieb et al, 2004), Bornstein, Becker-Matero, Winarick, and Reichman’s (2010) review of the literature on the relationship between performance-based measures of dependency and borderline pathology found that high levels of implicit dependency needs are typically present in BPD-diagnosed inpatients, but not in BPD-diagnosed outpatients. These contrasting patterns may suggest that BP-related dynamics differ somewhat in high- and lower-functioning patients with underlying borderline pathology (see also Bornstein et al, 2000, for evidence bearing on this issue). Alternatively, the experience of hospitalization may exacerbate dependency-related needs and fears in BPD patients, leading to increases in dependent imagery, and increases in ROD scores.…”
Section: Discussionmentioning
confidence: 99%
“…ROD scores have been shown to predict conformity, compliance, help seeking, and interpersonal yielding in a variety of situations (Bornstein et al, 2000). High scores on this scale have also been associated with increased sensitivity to interpersonal cues, an insecure attachment style, negative mood, and difficulty terminating psychotherapy (Bornstein et al, 2000). Results such as these continue to support the convergent validity of the ROD scale as a measure of interpersonal dependency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, both DPD and HPD are associated with high levels of underlying dependency strivings, but individuals with DPD are consciously aware of (and willing to acknowledge) these dependency needs whereas individuals with HPD are not. Such findings not only have implications for our understanding of the intrapsychic dynamics of these two forms of personality pathology, but also suggest possible avenues for psychotherapeutic intervention (see Bornstein, Hilsenroth, Padawer, & Fowler, 2000, Livesley, 2005). 3.…”
Section: Beyond Diagnosis: Multimodal Assessment Of Pdsmentioning
confidence: 93%